Concerns and Challenges Related to Sputnik V Vaccination Against the Novel COVID-19 Infection in the Russian Federation: The Role of Mental Health, and Personal and Social Issues as Targets for Future Psychosocial Interventions - Vasileva, Anna V.; Karavaeva, Tatiana A.; Radionov, Dmitriy S.; Yakovlev, Alexander V.; Mitin, Igor N.; Caroppo, Emanuele; Barshak, Sergey I.; Nazarov, Kirill S. (Frontiers in Psychiatry, 2022)
We carried out a cohort cross-sectional study of the population’s attitude towards vaccination against the novel COVID-19 coronavirus infection, using a specially designed questionnaire for online survey beginning two months after the start of mass vaccination in Russia and extending for six months. There were in total 4,977 respondents, ranging in age from 18 to 81 years. There were different tendencies in attitude to vaccination. Among respondents, 34.2% considered vaccination useful, 31.1% doubted its effectiveness, 9.9% considered vaccination unnecessary. The survey indicated that 7.4% of respondents were indifferent to the vaccine, while 12.2% deemed it to be dangerous. Nearly one third (32.3%) of respondents indicated that they did not plan to be vaccinated, while another third (34.0%) would postpone their decision until more comprehensive data on the results and effectiveness of vaccination were available. Only 11.6% of the respondents were vaccinated at the time of the study. Young people were less focused on vaccination compared to middle-aged and elderly people. The study results showed up vaccination attitudes interacted with individuals’ mental health. Factors associated with attitudes toward vaccination were age, gender, education, fear of possible complications, fear of contracting a coronavirus infection, concern for the health of relatives, and anxiety about the current situation with coronavirus in general. Insofar as reports of scientists, physicians, and experts are essential for shaping attitudes to vaccination, the study results inform the selection of target groups in need of particular psychosocial interventions to overcome their vaccine hesitancy.